PENGEMBANGAN PERANGKAT AJAR KURIKULUM MERDEKA PADA MATERI PEMANASAN GLOBAL DALAM MEMBANGUN MERDEKA BELAJAR - Faizah Al Munawwarah; Wiwit; Hermansyah Amir (ALOTROP, 2024)
This research is based on the limited references to existing independent curriculum teaching tools. This research aims to develop an independent curriculum teaching tool on global warming material to see the feasibility, response of educators and the effectiveness of the teaching tool. The type of research used is Research and Development (R&D) according to Sugiyono which consists of 10 stages, namely potential and problems, data collection, product design, design validation, design revision, small scale trials, product revisions, large scale trials, product revisions. , and mass production, but this research is limited to large-scale tests. The product in this research is a teaching tool, namely a teaching module. The research was conducted in April-September 2023 at MAN 1 Bengkulu City with the research subjects being class X 3 students at MAN 1 Bengkulu City, totaling 34 students. The research instruments used were interviews, validation sheets, response questionnaires and test instruments. The results of the teaching device feasibility test were said to be very valid with a score of 87.69%. The results of the educator response test were very good with a score of 91%, which educators felt was helpful in expressing the concept of global warming with simple experiments and was useful for students in building independent learning so as to increase understanding and learning outcomes in global warming material. The effectiveness of the teaching tools can be seen from the N-Gain, which is 0.618 in the medium category, which shows that the use of the Guided Discovery Learning-based independent curriculum teaching tools that were developed has proven to be effective in improving student learning outcomes on global warming material.